Utility of bile esculin azide agar for screening of stool samples for vancomycin resistant enterococci from patients with gut colonization - Devhare, Deepa Pramod; Pol, Sae Satish; Pendse, Varsha (International Journal of Research in Medical Sciences, 2021)
Background: Due to increased prevalence of vancomycin resistant enterococci (VRE) in hospital settings as an important nosocomial pathogen, microbiology laboratories should be prepared with test protocol for prompt detection and reporting of these resistant organisms. This helps in appropriate treatment of patients without delay and implementation of infection control measures in order to prevent spread of such infections. With this background present study was conducted to demonstrate utility of bile esculin azide agar with vancomycin (BEAV) for screening of enterococci for vancomycin drug resistance. Methods: Over a period of one year 200 stool samples were collected from hospitalized patients in a tertiary care hospital. Samples were inoculated on bile esculin azide agar with vancomycin (6ug/ml) to screen for vancomycin drug resistance in enterococci isolated from stool samples. Vancomycin drug resistance was confirmed by agar dilution method. Results: Out of 200 stool samples collected from hospitalized patients, 13 (6.5%) samples showed growth on bile esculin azide agar with vancomycin (6 µg/ml). Of these 13 isolates, 12 (92.3%) isolates were confirmed as VRE by agar dilution method and demonstrated minimum inhibitory concentration (MIC) of ≥32 µg/ml and all 12 isolates were identified as E. faecium. One (7.7%) isolate grown on BEAV was identified as E. gallinarum and showed MIC value of 8 µg/ml. Conclusions: Present study recommends use of bile esculin azide agar with vancomycin (6 µg/ml) as a screening medium for isolation of VRE from stool samples which usually carries mixed commensal flora of gastrointestinal tract.